Cellular Angiofibroma Presenting as a Subepithelial Rectal Mass. Issue 11 (19th November 2020) - Bloom, Jennifer; Jordan, Eric; Baratta, Vanessa M.; Zhang, Xuchen; Saha, Atin; Yavorek, George; Kurbatov, Vadim
ABSTRACT: A very rare case of cellular angiofibroma arising from the rectum in a 62-year-old man with a normal colonoscopy 2 years earlier is reported. To our knowledge, this is the first such case reported in the literature. The tumor was transanally excised with clear margins, and the patient had no postoperative complications. It is key to accurately differentiate this lesion from other subepithelial rectal tumors and more aggressive genital soft tissue tumors because clinical management varies. We performed a review of clinical records and pathology as well as an extensive literature review.